Medical terminology with human anatomy - Rice, Jane. (Stamford, CT : Appleton & Lange, 1999)
The fourth edition of this indispensable text provides comprehensive coverage of all aspects of medical terminology. Completely updated and revised, the book maintains its logical organization - material is arranged by body systems and specialty areas. Medical Terminology with Human Anatomy makes learning easy and interesting by presenting important prefixes, roots, and suffixes as they relate to each specialty or system, an approach that sets it apart from similar terminology texts. Detailed Terminology and Vocabulary sections make the text comprehensive.--Jacket.
1. Fundamental Word Structure -- 2. The Organization of the Body -- 3. The Integumentary System -- 4. The Skeletal System -- 5. The Muscular System -- 6. The Digestive System -- 7. The Cardiovascular System -- 8. Blood and the Lymphatic System -- 9. The Respiratory System -- 10. The Urinary System -- 11. The Endocrine System -- 12. The Nervous System -- 13. Special Senses: The Ear -- 14. Special Senses: The Eye -- 15. The Female Reproductive System -- 16. The Male Reproductive System -- 17. Oncology -- 18. Radiology and Nuclear Medicine -- App. III. Glossary of Component Parts.
Includes indexes.
Keywords: Human anatomy; Medicine; Nomenclature